2013
DOI: 10.1016/j.jdent.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a mouthwash containing 0.8% arginine, PVM/MA copolymer, pyrophosphates, and 0.05% sodium fluoride compared to a negative control mouthwash on dentin hypersensitivity reduction. A randomized clinical trial

Abstract: The results of this study support the conclusion that the Arginine Mouthwash provides a significant reduction in dentin hypersensitivity after eight weeks of product use as compared to a Negative Control mouthwash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 16 publications
1
29
0
4
Order By: Relevance
“…Light from an Er, Cr:YSGG laser is absorbed more strongly by OH ions of water molecules if the laser can cause an increase in the surface temperature, and this can hence alter the mineral content of the enamel and the dentin [38]. Freitas, et al recently indicated that low-power laser irradiation from an Er, Cr:YSGG laser at 0.25W or 0.5W allows the surface to become more resistant to acid consequent to changes in the structure of the enamel due to the chemical entities that are produced [13]. These authors hence speculated that Er, Cr:YSGG lasers can reduce DH in the long run due to the prevention of caries and due to effects on the decrease in solubility of the hard dental tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Light from an Er, Cr:YSGG laser is absorbed more strongly by OH ions of water molecules if the laser can cause an increase in the surface temperature, and this can hence alter the mineral content of the enamel and the dentin [38]. Freitas, et al recently indicated that low-power laser irradiation from an Er, Cr:YSGG laser at 0.25W or 0.5W allows the surface to become more resistant to acid consequent to changes in the structure of the enamel due to the chemical entities that are produced [13]. These authors hence speculated that Er, Cr:YSGG lasers can reduce DH in the long run due to the prevention of caries and due to effects on the decrease in solubility of the hard dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of an arginine-based mouthwash (0.8% arginine, PVM/MA copolymer, pyrophosphates, and 0.05% sodium fluoride) versus a placebo mouthwash without alcohol and without other components has shown that the arginine mouthwash provided a significant reduction in DH after eight weeks of use relative to a negative control mouthwash [13]. Other studies have shown that a toothpaste containing 8% arginine, calcium carbonate, and 1,450 ppm of sodium monofluorophosphate provided a greater efficacy in terms of reducing DH, relative to a desensitizing toothpaste containing 2% potassium ions [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formulation derived from this combination, Pro-Argin, has been described as a novel occlusion technology based on the fact that 8% arginine and calcium carbonate are believed to seal exposed dentinal tubules with a plug that contains arginine, calcium carbonate and phosphate thereby providing relief for DH [52]. This claim has been supported by the results of studies which demonstrated relief of DH for variable periods following the use of Pro-Argin mouthwash or paste [52,53]. Although previous systematic reviews have recommended arginine-containing toothpastes for treatment of DH [50,51].…”
Section: Recent Developments In the Treatment Of Dentine Hypersensitimentioning
confidence: 99%